Nordic alcohol policy in Europe : the adaptation of Finland's, Sweden's and Norway's alcohol policies to a new policy framework, 1994-2013 - Karlsson, Thomas (Research / National Institute for Health and Welfare, ISSN 1798-0054, 2014)
Abstract.
Keywords: 1990-luku; 2000-2009; 2010-luku; alkoholi; alkoholipolitiikka; alkoholilaki; yhdenmukaistaminen; eurooppalaistuminen; alkoholinkäyttö; tuontirajoitukset; sisämarkkinat; alkoholpolitik; alkoholanvändning; europeisering; Pohjoismaat; Suomi; Ruotsi; Norja; Norden